Optimization of Agroinfiltration in Pisum sativum Provides a New Tool for Studying the Salivary Protein Functions in the Pea Aphid Complex - Guy, Endrick; Boulain, Hélène; Aigu, Yoann; Le Pennec, Charlotte; Chawki, Khaoula; Morlière, Stéphanie; Schädel, Kristina; Kunert, Grit; Simon, Jean-Christophe; Sugio, Akiko (Frontiers in Plant Science, 2016)
Aphids are piercing-sucking insect pests and feed on phloem sap. During feeding, aphids inject a battery of salivary proteins into host plant. Some of these proteins function like effectors of microbial pathogens and influence the outcome of plant–aphid interactions. The pea aphid (Acyrthosiphon pisum) is the model aphid and encompasses multiple biotypes each specialized to one or a few legume species, providing an opportunity to investigate the underlying mechanisms of the compatibility between plants and aphid biotypes. We aim to identify the aphid factors that determine the compatibility with host plants, hence involved in the host plant specialization process, and hypothesize that salivary proteins are one of those factors. Agrobacterium-mediated transient gene expression is a powerful tool to perform functional analyses of effector (salivary) proteins in plants. However, the tool was not established for the legume species that A. pisum feeds on. Thus, we decided to optimize the method for legume plants to facilitate the functional analyses of A. pisum salivary proteins. We screened a range of cultivars of pea (Pisum sativum) and alfalfa (Medicago sativa). None of the M. sativa cultivars was suitable for agroinfiltration under the tested conditions; however, we established a protocol for efficient transient gene expression in two cultivars of P. sativum, ZP1109 and ZP1130, using A. tumefaciens AGL-1 strain and the pEAQ-HT-DEST1 vector. We confirmed that the genes are expressed from 3 to 10 days post-infiltration and that aphid lines of the pea adapted biotype fed and reproduced on these two cultivars while lines of alfalfa and clover biotypes did not. Thus, the pea biotype recognizes these two cultivars as typical pea plants. By using a combination of ZP1109 and an A. pisum line, we defined an agroinfiltration procedure to examine the effect of in planta expression of selected salivary proteins on A. pisum fitness and demonstrated that transient expression of one candidate salivary gene increased the fecundity of the aphids. This result confirms that the agroinfiltration can be used to perform functional analyses of salivary proteins in P. sativum and consequently to study the molecular mechanisms underlying host specialization in the pea aphid complex.